Enhancing flexibility through an adapted fitness programme within the framework of practical physical culture classes - Udalova, M.A.; Morozova, L.V.; Kiryanova, L.A.; Khilchenko, A.D. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to develop and experimentally substantiate the effectiveness of an adapted fitness programme for improving flexibility in female university students. Methods and structure of the study. The research employed analysis of literature sources, pedagogical observation, a respondent survey aimed at identifying the most popular fitness technologies among students, pedagogical testing designed to assess the level of active and passive flexibility, a pedagogical experiment, and mathematical-statistical data processing. The study involved third-year female students from the Faculty of International Relations and Political Studies, assigned to the primary and preparatory health groups (n=68). Results and conclusions. An adapted fitness programme for flexibility development was designed, which contributed to increasing the range of motion in various joints. Assessment exercises for determining active and passive flexibility in female students were developed. The application of the adapted fitness programme in the educational process enables proportional development of physical abilities, formation of aesthetic qualities, health-improving effects and body composition improvement, as well as increasing sustained interest in practical physical education classes at university.